The Stress and Vascular Catastrophes in Newborn Rats: Mechanisms Preceding and Accompanying the Brain Hemorrhages - Semyachkina-Glushkovskaya, Oxana; Borisova, Ekaterina; Abakumov, Maxim; Gorin, Dmitry; Avramov, Latchezar; Fedosov, Ivan; Namykin, Anton; Abdurashitov, Arkady; Serov, Alexander; Pavlov, Alexey; Zinchenko, Ekaterina; Lychagov, Vlad; et al. (Frontiers in Physiology, 2016)
In this study, we analyzed the time-depended scenario of stress response cascade preceding and accompanying brain hemorrhages in newborn rats using an interdisciplinary approach based on: a morphological analysis of brain tissues, coherent-domain optical technologies for visualization of the cerebral blood flow, monitoring of the cerebral oxygenation and the deformability of red blood cells (RBCs). Using a model of stress-induced brain hemorrhages (sound stress, 120 dB, 370Hz), we studied changes in neonatal brain 2, 4, 6, 8 hrs after stress (the pre-hemorrhage, latent period) and 24 hrs after stress (the post-hemorrhage period). We found that latent period of brain hemorrhages is accompanied by gradual pathological changes in systemic, metabolic and cellular levels of stress. The incidence of brain hemorrhages is characterized by a progression of these changes and the irreversible cell death in the brain areas involved in higher mental functions. These processes are realized via a time-depended reduction of cerebral venous blood flow and oxygenation that was accompanied by an increase in RBCs deformability. The significant depletion of the molecular layer of the prefrontal cortex and the pyramidal neurons, which are crucial for associative learning and attention, is developed as a consequence of homeostasis imbalance. Thus, stress-induced processes preceding and accompanying brain hemorrhages in neonatal period contribute to serious injuries of the brain blood circulation, cerebral metabolic activity and structural elements of cognitive function. These results are an informative platform for further studies of mechanisms underlying stress-induced brain hemorrhages during the first days of life that will improve the future generation’s health.